Activity of hydrothermal fluid at the bottom of a lake and its influence on the development of high-quality source rocks: Triassic Yanchang Formation, southern Ordos Basin, China. Issue 1 (2nd January 2020) - You, J.; Liu, Y.; Zhou, D.; Zheng, Q.; Vasichenko, K.; Chen, Z.
Abstract: Evidence for hydrothermal activity, such as siliceous rocks, iron dolomite layer deposits, and hydrothermal mineral combinations of ilmenite + pyrite + anhydrite, has been found in the high-quality source rocks from the Chang 7 layer in the Triassic Yanchang Formation from the southern margin of the Ordos Basin, China. In this paper, elemental geochemical analysis is carried out on a large number of samples collected from an outcrop geological section and drill core from the Chang 7 layer. We use elemental ratios to study the hydrothermal activity; the Al/(Al + Fe + Mn) ratio reflects the paleoproductivity, and the P/Al and P/Ti ratios and total S contents reflect the redox environment. The relationships between the hydrothermal activity and paleoproductivity, redox conditions and organic matter content are discussed. The correlation coefficients between the hydrothermal index Al/(Al + Fe + Mn) and the (Fe + Mn)/Ti ratio and total organic carbon are as high as –0.88 and 0.87, respectively, demonstrating a close relationship between hydrothermal activity and source-rock deposition. The correlation coefficients between the Al/(Al + Fe + Mn) ratio and the P/Al and P/Ti ratios, and total S contents are –0.81, –0.80, and –0.89, respectively, supporting this relationship. Hydrothermal activity can promote productivity at the lake surface and the development of a bottom-water anoxic environment. The paleoproductivity level of the Chang 7 sedimentary period is relatively high and represents an oxygen-poor anaerobic environment. The hydrothermal activity in the southern margin of the basin is strong, whereas the activity in the north is gradually weakened. Studies have shown that the hydrothermal activity at the bottom of the lake plays an important role in promoting the large-scale development of the Chang 7 high-quality source rocks. The organic matter abundance in samples with hydrothermal alteration are greater than in samples elsewhere.